The electrochemical reduction of indigo dissolved in organic solvents and as a solid mechanically attached to a basalt plane pyrolytic graphite electrode immersed in aqueous electrolyte solution - Bond, A; Marken, F; Hill, E; Compton, R; Hugel, H (1997)
The electrochemical properties of solid materials such as organic compounds, irrespective of their electrical conductivity, can be studied via the use of submicron sized particles mechanically attached to electrode surfaces immersed in aqueous media containing different electrolytes. In this study the reduction of solid indigo in buffered and non-buffered aqueous media has been investigated. Data are compared to those obtained from a voltammetric study of indigo dissolved in dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF) and in pyridine and the interpretation of results is facilitated by in situ EPR, in situ UV-VIS spectroscopy and atomic force microscopy (AFM) studies. For the reduction of solid indigo two distinct types of reduction processes, 'surface-type' and 'bulk-type', have been observed. The latter process has been found to be associated with the reductive dissolution of indigo. The 'surface-type' responses which occur in a microphase at the electrode/solid/solution interface are reversible 2H+-2e- reduction and oxidation processes with a corresponding 60 mV shift in half wave potential per pH unit in buffered electrolyte media over the pH range 4 to 11. The 'bulk-type' reduction process is proposed to be associated with the electroinsertion of cations into the solid indigo particles, thereby producing a reduced material and causing the loss of material from the electrode surface under convective flow conditions. The electrochemical solubilization of indigo occurred in non-buffered aqueous media even at neutral pH values.